الترادف في اللغة العربية - Muhammad Ediyani ('ARABIYYA: JURNAL STUDI BAHASA ARAB, 2017)
Synonym is one of the most important linguistic phenomena in terms of the meanings of the words in terms of the impact of communication between people. Synonym issues were intertwined with the interest of scholars. They views differed, and their trends differed, including linguists, jurists, scholars and practitioners of Qur'anic sciences. For this, the learner must learn and know deeply about the synonyms in Arabic. This search of desktop research is a way of observing the various books. The results of the research are divided between supporters and opponents of the following: a team that agrees with tandem, but in tandem, a team that denies the existence of tandem in the language completely, a team that proves the tandem at all. The researcher is based on the existence of tandem in the Arabic language, but it is a tandem in the sense of convergence in meaning, on the basis that each word has a particular meaning and useful or special function in their use.